2001
DOI: 10.2337/diacare.24.10.1776
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Fidarestat, a Novel Aldose Reductase Inhibitor, for Diabetic Peripheral Neuropathy

Abstract: A 52-week multicenter placebo-controlled double-blind parallel group study OBJECTIVE -The purpose of this study was to evaluate the efficacy of fidarestat, a novel aldose reductase (AR) inhibitor, in a double-blind placebo controlled study in patients with type 1 and type 2 diabetes and associated peripheral neuropathy.RESEARCH DESIGN AND METHODS -A total of 279 patients with diabetic neuropathy were treated with placebo or fidarestat at a daily dose of 1 mg for 52 weeks. The efficacy evaluation was based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(123 citation statements)
references
References 27 publications
5
112
0
4
Order By: Relevance
“…The results, consistent with previous reports on the alleviation of diabetic complications with fidarestat treatment (63)(64)(65)(66), support a pathogenetic, rather than protective, role for increased aldose reductase activity in diabetic cataractogenesis and early retinopathy, and provide a rationale for the development of aldose reductase inhibitors, and, in particular, fidarestat, for their prevention and treatment.…”
Section: Discussionsupporting
confidence: 80%
“…The results, consistent with previous reports on the alleviation of diabetic complications with fidarestat treatment (63)(64)(65)(66), support a pathogenetic, rather than protective, role for increased aldose reductase activity in diabetic cataractogenesis and early retinopathy, and provide a rationale for the development of aldose reductase inhibitors, and, in particular, fidarestat, for their prevention and treatment.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, a 52-week multicenter (78 centers in Japan) placebo-controlled double-blind parallel group study of the AR inhibitor fidarestat in 279 patients with type 1 and type 2 diabetes and associated peripheral neuropathy revealed beneficial effects of treatment on subjective symptoms including numbness, spontaneous pain, sensation of rigidity, paresthesia in the sole upon walking, heaviness in the foot, and hypesthesia. 105 Similar results have been achieved in the 3-year, multicenter (112 centers in Japan), comparative Aldose Reductase InhibitorDiabetes Complications Trial in 594 subjects with diabetic neuropathy, in which numbness of limbs, sensory abnormalities, and cramping were alleviated in patients treated with the AR inhibitor epalrestat compared with the placebo group. 106 A more recent open-label pilot study (12 hospitals in Japan, 22 patients) revealed beneficial effect of fidarestat on vibration perception threshold of the upper and lower limbs and subjective symptoms of PDN, such as severity of numbness in the lower limbs, heaviness in the foot, coldness and hot flushes in the lower limbs, smarting pain causing difficulty in walking, sensation as if walking on sand, sensation as if walking on an uneven road, spontaneous pain in the lower limbs, and dizziness.…”
Section: Summary Of the Current Knowledge On The Key Mechanisms Of DIsupporting
confidence: 67%
“…35,36 Glutamate concentrations in the peripheral nerve system are reduced by AR inhibitor, 35 vasodilator, 122 and antioxidant 123 treatments-and all these treatments also alleviate symptoms of diabetic neuropathic pain in diabetic animal models 19,20 -22,77,78,99,102 and in human subjects. [105][106][107]111,112,114,124 Several reports indicate that the pro-inflammatory cytokine tumor necrosis factor alpha (TNF-␣) plays a role in nondiabetic painful neuropathy. [125][126][127] It is quite plausible that it also plays a role in diabetic neuropathic pain (as has been suggested 128,129 ), because TNF-␣ expression is increased in tissues of diabetic animals, and TNF-␣ induces overexpression of cyclooxygenase-2, 130,131 also implicated in diabetic hyperalgesia and allodynia.…”
Section: Strategies For Drug Discoverymentioning
confidence: 99%
“…Our data showed significant effects on both NO and NBF. A previous study reported that fidarestat had stronger aldose reductase inhibition and longer half-life in the peripheral nerve than other ARIs [32]. These points could explain why fidarestat is more effective on NO and NBF in improving conduction velocity.…”
Section: Discussionmentioning
confidence: 81%
“…Fidarestat is active in several sites of action. It is a powerful ARI and reduces polyol accumulation [32]. The other mechanism is the polyol pathway being active in the endothelial cell.…”
Section: Discussionmentioning
confidence: 99%